Punción Seca en Punto Gatillo - Diana Alexandra, Paguay Llamuca (2021)
ABSTRACT In this research work under the title Dry Needling at Trigger Point, the use of the dry needling technique in patients with myofascial pain is analyzed by collecting information from 39 articles, magazines, books that provide information on dry needling in trigger points, which will be selected by means of the ACC (Average Count Citation) function, PEDro and SJR (Scimago Journal Ranking) scale. The cause of myofascial pain can produce a disability, and the use of the deep dry needling technique helps in reducing hyperirritability and in improving the functional area of the affected area; leading to a better quality of life. In the research, it can be observed that the deep dry needling technique has greater benefits for the reduction of myofascial pain and these results are observed in less time. The methodology proposed by the investigative work is the logical deductive and analytical one, which is why it focuses on collecting information on dry needling and trigger points through a selection with a qualitative, non-experimental and descriptive type of study, mainly by the articles obtained in the inquiry, which were 180 at the beginning of the research and the articles that comply with the assessment of the PEDro scale 39 ones were finally selected for the preparation of the bibliographic project. When selecting the 39 articles for research, these included the application of superficial dry needling, deep dry needling and comparison with other techniques, determining the decrease in myofascial pain. When analyzing and classifying them, frequent positive results were observed with a longer time in the application of deep dry needling, and the use of superficial dry needling in less time in relation to mobility and comparison to this technique. Bearing in mind that this method is debatable, but it offers positive results in the short and medium term. Keywords: dry needling, miofascial point, semiology, trigger points, miofascial syndrome, endogenous systems, semi-invasive. Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301